The Refining Capability of Palm Shell Activated Carbon for Waste Cooking Oil - Maria Ulfah; Chrisatya Nugraha Tamanampo; Sunardi Sunardi (Food ScienTech Journal, 2023)
The high level of consumption of cooking oil will have an impact on increasing the waste of cooking oil produced. Using the waste of cooking oil needed purification, including through the adsorption process using activated carbon. This research aimed to study the ability of palm kernel shell activated carbon (PKSAC-AC260) compared to standard activated carbon (DAC or Decolorized Activated Charcoal by Sigma-Aldrich) in refining waste cooking oil at various concentrations of activated carbon. The results showed that the type of activated carbon influenced color, free fatty acid content, peroxide value, and saponification value of purified waste cooking oil, but had no effect on water content, saponification value and iodine value. Activated carbon between PKSAC-AC260 and DAC with a concentration of 2.5% was able to improve the quality of the best waste cooking oil. Purification of used cooking oil using PKSAC-AC260 and DAC was able to increase the color brightness of waste cooking oil (∆E) by 5.44 and 4.53, reduce the free fatty acid content of waste cooking oil from 1.47% to 0.79% and 0.61%, reduce the peroxide value of waste cooking oil from 163.47 meq/kg to 116.40 meq/kg and 98.82 meq/kg, and increase the saponification value of waste cooking oil from 155.22 mg/g to 180.48 mg/g and 184.48 mg/g, respectively. The ability of PKSAC-AC260 to purify waste cooking oil is lower than that of DAC. The quality of processed oil from waste cooking oil does not meet the quality standards of cooking oil based on SNI 3741: 2013.